A cartoon for life - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Reaping without weeping: a guide to safe management and application of chemicals in agriculture by the Caribbean Network for Integrated Rural Development (CNIRD) 1991